Ethos e Pathos em Schopenhauer e Nietzsche: vida, vontade e ascetismo - Moreira, Fernando de Sá (2011)
This dissertation investigates the conception of asceticism on two German philosophers, Arthur Schopenhauer and Friedrich Nietzsche. Whereas there isn't a precise language to mediate this two philosophies, we apply the concepts of pathos and ethos to make a dialog between the German philosophers, which allow us to investigate how these concepts appear in the cosmological and ethical parts of their theories. Especially in the Nietzsche's philosophy, we concentrate the researches on his third period. We use mainly the books Genealogy of Moral, Beyond Good and Evil and The Antichrist. About Schopenhauer's books, we use mainly the two volumes of The World as Will and Representation. Our conclusion is that, on Schopenhauer's doctrine, the cosmological effectiveness (Wirklichkeit) is pathos, but the metaphysical reality (Realität) is ethos. Therefore the asceticism is a sui generis pathos on Schopenhauer: when the will extraordinarily makes a turn, it makes the negation of the will, it does not become an absolute nothing. It become a relative nothing, a negative pathos. The same does not occur to Nietzsche. According to the philosopher of the will to power, the will never negates itself. All the effectiveness is always pathos and there is no ethos: the world is always pathos, in all aspects. The asceticism is an ordinary case of the will to power (Wille zur Macht) and the ascetic pathos is merely a strategy of a form of life to conserve itself in existence.